Significance Christ Centric Hermeneutics on the Problem of Grief Mediated by Psychotherapy and Logotherapy in South Tangerang City - Thomas Kartomo (International Perspectives in Christian Education and Philosophy, 2024)
This writing aims to prove that Christ Centric ideas when integrated with psychotherapy and logotherapy are effective in overcoming the problem of losing a loved one and will produce a significant level of recovery. Through this research, it is shown that people who grieve when carrying out several activities, such as listening to sermons, reading the Bible, singing, and carrying out social-diaconal actions; their faith has been strengthened (orthodoxy), their enthusiasm for carrying out religious and social activities (orthopraxy), they are more sensitive to other people (ortopathy), and they have increased their ability to do good deeds (pietas). Therefore, the church needs to involve grieving people in church activities, because by involving them, it also means helping them to speed up the process of recovery from grief. Academically, the idea of ​​Christ Centric theology can be justified. Through an exegetical study of Colossians 1:15-20, it has been proven that Christ is central and primary in all forms of God's plans and actions. Both in the creation event, maintenance of creation after the fall into sin, redemption, and salvation; Christ is the center and ultimate. Thus, Christ Centric theology is worthy of being applied in Christian counseling and psychotherapy.